2009
DOI: 10.1080/09712119.2009.9706977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Characteristics of Chukar Partridges(Alectoris chukar)Raised in Captivity

Abstract: Balcioglu, M.S., Kizilkaya, K., Karabag, K., Alkan, S., Yolcu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
2
6
3
Order By: Relevance
“…Sexual dimorphism has previously been reported in favour of the male in duck [23], pigeon [24], and pheasants [25,26]. The growth pattern of male and female Japanese quails raised in other environments have been well documented [20,[27][28][29]. The growth pattern observed in the present study agrees with the pattern reported in refs.…”
Section: Discussionsupporting
confidence: 91%
“…Sexual dimorphism has previously been reported in favour of the male in duck [23], pigeon [24], and pheasants [25,26]. The growth pattern of male and female Japanese quails raised in other environments have been well documented [20,[27][28][29]. The growth pattern observed in the present study agrees with the pattern reported in refs.…”
Section: Discussionsupporting
confidence: 91%
“…The growth patterns of male and female were different (Soner Balcioğlu et al 2009), therefore, data set was analyzed for each gender and population. Estimated growth curve parameters of total partridges, females and males for the nine growth models utilized were presented on Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Humans generally consume table eggs, but in small quantities, they consume fertile eggs from other poultry species. In recent years consumer interest has increased for quail, pheasant and partridge eggs (Balcioğlu et al, 2009;Garip et al, 2010;Karabag et al, 2010;Burden, 2013;Kokoszyński, 2017). The structure of the egg is similar in various poultry species, but there are differences in the proportions of these parts (Nys and Guyot, 2011).…”
Section: Introductionmentioning
confidence: 99%